Affected Potentials: The Dimensions of Incipient Homosexuality and Foundational Affect in Contemporary Gay Literature - Lawless, Evan Patrick (Curtin University, 2023)
Affected Potentials explores the relationship between incipient homosexuality and the affects of shame, anxiety and loneliness that underpin it in contemporary literature. Through a closed-text analysis, it is argued that these affects are central to the representation of developing homosexuality in literature and provide the foundation for exploring queer resistance of heteronormativity.